Perencanaan Ulang Struktur Portal Utama Gedung PT. Ferron Par Pharmaceuticals Cikarang Integrasi BIM (Building Information Modelling) - Nabila Alsa Fernanda; Rendi Dwi Pratama; Asri Nurdiana; Bambang Setiabudi (Jurnal Sipil dan Arsitektur, 2023)
In development construction projects, the digitalization of excellent and mature construction planning is needed to obtain efficient and effective construction results and through the implementation of BIM integrated Structural Planning and Analysis(Building Information Modelling) expected in building planning PT. Ferron Pharmaceuticals Cikarang can minimize the occurrence of errors. The purpose of this final project is to re-design the building of PT. Ferron Pharmaceuticals Cikarang by integrating conventional planning methods into a based planning method BIM (Building Information Modelling) for efficiency structure and project visualitation on the project. The process used is quantitative descriptive by conducting a literature study to understand the basics of planning a high-rise building structure, then proceeding with integration based on SAP2000. The result of this paper is an earthquake-resistant structural design with the Sway Frame with modelling 3D that can be applied to tall buildings with high levels of security, reliability and earthquake resistance. The Finding of this re-design is the high efficiency of this structure in reducing earthquake resistance and can be used as a reference for planning earthquake resisitant buildings in the future.